Exploring patient and clinician perspectives on the benefits and risks of emerging therapies for the treatment of haemophilia: a qualitative study - Spoors John; Payne Katherine; Wright Stuart; Horsley Will; Bell Sadie; Cairns John (The Journal of Haemophilia Practice)
Enhanced horizon scanning for emerging treatments has identified that both haemophilia A and haemophilia B pathways will be enriched with a range of new medicines with varying benefit-risk profiles. Patient and clinician views on the balance of the benefits and risks associated with emerging therapies will affect their use for the treatment of haemophilia, while also introducing the need for effective communication strategies to enable informed patient-clinician decision-making.